Efeitos do contaminante emergente nonilfenol etoxilado (NPE) em múltiplos biomarcadores em girinos de rã-touro (Aquarana catesbeiana) sob o cenário do aquecimento global - Gonçalves, Yan Costa (Universidade Federal de São Carlos, 2025)
The global decline in amphibian populations has been extensively documented and is attributed to a complex interplay of environmental factors. Among these, chemical pollution from emerging contaminants, such as nonylphenol ethoxylate (NPE), combined with the increase in surface water temperatures due to climate change, stands out. These factors, acting synergistically, may exacerbate the significant decline in amphibian species. NPE, a surfactant widely used in the formulation of sanitary products, has frequently been detected in Brazilian aquatic ecosystems at alarming concentrations, exceeding international regulations. Despite its environmental relevance, there is a gap in knowledge regarding the sublethal effects of NPE on amphibians, particularly under thermal stress conditions. This study aimed to investigate the sublethal effects of acute exposure (48 h) to an environmentally relevant concentration of NPE (30 µg L-1) on Aquarana catesbeiana tadpoles at Gosner stage 25, under two distinct thermal conditions (25°C and 30°C), as well as to evaluate the interaction between these factors (NPE × temperature). Multiple biomarkers were analyzed: biometric indices (Fulton’s condition factor [K], hepatosomatic index [HSI], and relative ventricular mass [RVM]), physiological biomarkers (heart rate [fH], ventricular contraction force [Fc], cardiac pumping capacity [CPC], contraction rate [+dF/dt], and relaxation rate [-dF/dt]), biochemical biomarkers (activity of the antioxidant enzymes superoxide dismutase [SOD], catalase [CAT], glutathione S-transferase [GST], and glutathione peroxidase [GPx]; reduced glutathione content [GSH]; levels of lipid peroxidation [LPO] and protein carbonylation [PC] in hepatic, branchial, and muscular tissues), and neurotoxic biomarkers (acetylcholinesterase [AChE] activity in the brain and muscle). Exposure to NPE induced hepatotoxic effects (reduction in HSI and antioxidant defenses), cardiotoxic effects (reductions in RVM, Fc, +dF/dt, and -dF/dt), tachycardia, alterations in the antioxidant defense system, and oxidative stress in the gills and muscle, as well as inhibition of muscular AChE. The increase in temperature intensified the negative inotropic effect, depleted branchial antioxidant defenses, and exacerbated oxidative stress in the liver and muscle, in addition to causing central neurotoxicity. These results indicate that in environments contaminated with NPE, rising temperatures associated with climate change may aggravate the sublethal effects of NPE, even after short-term exposure. The absence of regulations for safe NPE concentrations in Brazilian legislation, coupled with global warming, represents a critical threat to biodiversity, particularly for amphibians, highlighting the urgent need for environmental guidelines and mitigation strategies.
Effects of the emerging contaminant nonylphenol ethoxylate (NPE) on multiple biomarkers in bullfrog tadpoles (Aquarana catesbeiana) under the scenario of global warming
Keywords: Anfíbios; Contaminante emergente; Mudanças climáticas; Função cardíaca; Estresse oxidativo; Hepatotoxicidade; Neurotoxicidade; Amphibians; Emerging contaminant; Climate changes; Cardiac function; Oxidative stress; Hepatotoxicity; Neurotoxicity; CIENCIAS BIOLOGICAS::FISIOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA COMPARADA